Microwave-Assisted Synthesis of Heterocycles Using 1,8-Diazabicyclo[5.4.0]undec-7-ene (DBU) - Yadav, Parul; Singh, Ram (Current Microwave Chemistry, 2025)
: 1,8-Diazabicyclo[5.4.0]undec-7-ene (DBU) is a non-nucleophilic base and belongs to the class of amidine compounds. DBU is involved in the synthesis of a variety of biologically active compounds either alone or in combination with microwaves. The use of microwave (MW) irradiation in organic synthesis is covered under the principles of green chemistry. The DBU in combination with MW has been utilized in the synthesis and/or derivatization of many biologically active five-membered, six-membered, and other heterocycles. This review article discusses the utilization of DBU in combination with MW in the synthesis of compounds, like benzoxanthones, indoles, benzimidazoles, isoindolin-1-one, isatins, and so on. This article also covers the transformation of group(s) linked to heterocyclic compounds using MW and DBU.
Keywords: benzimidazoles